DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN RUSSIAN LANGUAGE TEACHING: STRATEGIES AND PRACTICES (Neo Science Peer Reviewed Journal, 2023)
Development of communicative competence in Russian language teachingThe development of technologies inevitably leads to changes in the educational sphere. Today's students live in the digital age, so the use of modern technologies in Russian language learning becomes an integral component of a successful educational process. It helps teachers to make lessons more interactive, attractive and effective for students.